CFD Modeling Optimizes Water Treatment Plant Performance. Issue 7 (1st July 2019) - Wicklein, Edward; Hart, Vincent; Carter, Elizabeth; Haight, Ralph; Oligo, Bobby; Watson, Kirk
Abstract : CFD modeling helped a colorado utility optimize the hydraulic efficiency of its water treatment plant.